PENGGUNAAN SALIVA UNTUK MENDETEKSI KANKER - Herlia Nur Istindah; Eliza Ibrahim Auerkari (Faculty of Dentistry, Universitas Indonesia, 2015)
Cancer detection medium such as serum & biopsy often make ptient uncooperative due to lack of safety, convenience & economic. This condition causes cancer to be detected at late stadium and causes death. This paper discusses the role of saliva as cancer detection medium of choice. Some tumor markers have been identified in saliva such as C-erbB-2, CA 15-3, P53 and CA 125. Each corresponds to certain type of cancer. These tumor markers are protein, this the use of saliva to detect cancer can utilize protein analysis technique such as ELISA. ELISA can be used for early detection and monitoring of the effectiveness of breast cancer treatment by showing the expression of c-erbB-2 & CA 15-3 in saliva. Saliva has high potential as cancer detection medium & cancer treatment monitor, especially breast cancer. Further various researches are needed for different tumor marker with other protein analysis technique.